2021
DOI: 10.1007/s13300-021-01079-x
|View full text |Cite
|
Sign up to set email alerts
|

Generalizability of the Results of Cardiovascular Outcome Trials of Glucagon-Like Peptide 1 Receptor Agonists in Chinese Patients with Type 2 Diabetes Mellitus

Abstract: Introduction: This study aimed to investigate the generalizability of the results of cardiovascular outcome trials (CVOTs) of glucagon-like peptide 1 receptor agonists (GLP-1 RAs) to Chinese patients with type 2 diabetes mellitus (T2DM). Methods: The 3B (Blood Glucose, Blood Pressure, and Blood Lipid) population, a nationally representative population of patients with T2DM in China (n = 25,411), was examined for eligibility of enrollment in four GLP-1 RAs CVOTs (Dulaglutide-REWIND, Exenatide-EXSCEL, Liraglutid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…It may also lead to heart, brain, kidney, eye, liver, vascular and other organ injuries. [ 54 ] The prolonged and sustained hyperglycemic state will aggravate or accelerate the liver damage. It causes a gradual development of fatty liver, liver fibrosis and even liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…It may also lead to heart, brain, kidney, eye, liver, vascular and other organ injuries. [ 54 ] The prolonged and sustained hyperglycemic state will aggravate or accelerate the liver damage. It causes a gradual development of fatty liver, liver fibrosis and even liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…Asian Indians are more susceptible to develop T2DM than Chinese and Malays and when diabetes mellitus occurs, the risk of ischaemic heart disease is higher than for their Chinese and Malays counterparts ( 28 ). Of note, a study reported that ≤15% of a nationally representative population of patients with T2DM in China would have been eligible for enrolment in three CVOTs with GLP-1RAs considered in a previous meta-analysis ( 22 ), thus questioning about the generalizability of CVOTs results to Chinese patients with T2DM ( 29 ).…”
Section: Unanswered Questions Related To Race/ethnic Differencesmentioning
confidence: 99%
“…5 In addition, among four GLP-1 RA CV outcome trials, the REWIND trial of once-weekly dulaglutide is the most generalizable to Chinese patients with T2DM. 6 Once-weekly dulaglutide is an optimal treatment for Chinese patients with T2DM inadequately controlled by 1-2 oral antidiabetes treatments according to the primary findings and post-hoc analyses of AWARD-CHN2. [2][3][4] However, patients participating in randomized, controlled trials are highly selected, based on the inclusion/exclusion criteria, and these studies are performed under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, evidence to support primary prevention of CVD events is not available for other GLP‐1 RAs 5 . In addition, among four GLP‐1 RA CV outcome trials, the REWIND trial of once‐weekly dulaglutide is the most generalizable to Chinese patients with T2DM 6 . Once‐weekly dulaglutide is an optimal treatment for Chinese patients with T2DM inadequately controlled by 1‐2 oral antidiabetes treatments according to the primary findings and post‐hoc analyses of AWARD‐CHN2 2–4 .…”
Section: Introductionmentioning
confidence: 99%